2008
DOI: 10.1139/s08-002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal occurrence and removal of polycyclic and nitro musks from wastewater treatment plants in Ontario, Canada

Abstract: Polycyclic and nitro musk (PNM) fragrances in personal care products persist and bioaccumulate in the environment following wastewater discharges and land application of biosolids. Influent and effluent concentrations, seasonal variations, and process removal efficiencies of 11 PNMs were investigated at six wastewater treatment plants representing four typical Canadian treatment processes: lagoon, oxidation ditch, extended aeration, and conventional activated sludge. Influent concentrations were as high as 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
4
11
0
Order By: Relevance
“…Concerns over the toxicity and bioaccumulation of NMs lead to restrictions on their appliance in cosmetics. However, they were still added in many cheap consumer products, leading to their presence in environmental samples and biota (Raab et al, 2008;Smyth et al, 2008). Compared with one previous study, which reported that the mean concentrations of MX (DF: 80%) and MK (DF: 90%) were 10.4 and 46.3 ng/g in sludge from Guangdong Province of China , while these two compounds in our study had lower DFs (14% for MX and 29% for MK) but higher mean concentrations exceeding LOQ (382 for MX and 359 ng/g dw for MK).…”
Section: Concentrations and Composition Profiles Of Sms In Sludgementioning
confidence: 99%
“…Concerns over the toxicity and bioaccumulation of NMs lead to restrictions on their appliance in cosmetics. However, they were still added in many cheap consumer products, leading to their presence in environmental samples and biota (Raab et al, 2008;Smyth et al, 2008). Compared with one previous study, which reported that the mean concentrations of MX (DF: 80%) and MK (DF: 90%) were 10.4 and 46.3 ng/g in sludge from Guangdong Province of China , while these two compounds in our study had lower DFs (14% for MX and 29% for MK) but higher mean concentrations exceeding LOQ (382 for MX and 359 ng/g dw for MK).…”
Section: Concentrations and Composition Profiles Of Sms In Sludgementioning
confidence: 99%
“…Low LOD and LOQ are obtained for the non-polar organic compounds such as musks for Ternes and Salgado in [9,19], when analysed by GC-MS as well as the recoveries were very high as presented in Table 1 for Smyth and Salgado in [9,39].…”
Section: Calibration Curves Limits Of Detection (Lod) and Quantificamentioning
confidence: 99%
“…In general it is agreed that most synthetic musks have minimal direct effects on human and environmental health, but concerns are raised by their bioaccumulation and possible effects at those higher levels (Ternes and Joss 2006). In WWTPs, musks will generally adsorb to sludge (Lishman et al 2007;Moffat et al 2004).…”
Section: Ppcps Effects On Wildlife and Human Healthmentioning
confidence: 99%
“…Specific studies of surface waters and wastewater treatment plants were conducted in several provinces, including BC, Alberta (Sosiak and Hebben 2005), Ontario (Metcalfe et al 2003a;Metcalfe et al 2003b;Ternes et al 1999), Quebec and Atlantic provinces. Typical treatment technologies addressed included conventional activated sludge, extended aeration activated sludge, lagoons, oxidation ditches, ultrafiltration and nanofiltration membranes, ozonation, and various stages of aerobic digestion of municipal wastewater sludge (e.g., Lishman et al 2007;Smyth et al 2007;Citulski and Farahbakhsh 2007). Thus, a general assessment of principal sources of common PPCPs and approximate levels of removal by various treatment processes is available.…”
Section: Current Canadian Research Directions On Ppcps In Urban Watersmentioning
confidence: 99%
See 1 more Smart Citation